The Epistolary Novel in Eighteenth-Century Russia - Fraanje, Maarten (Vortraege und Abhandlungen zur Slavistik, 2001)
The series Lectures and Treatises on Slavic Studies, which has been published since 1980, offers opportunities for publication, especially for smaller monographs, which, in terms of their scope, are located between the journal article and the large book. It will cover topics from the whole area of ​​Slavic languages, literatures and cultures as well as their interrelations. In addition to investigations, bibliographies, research reports and editions are published. The authors of the previous volumes come from America, Canada, Germany, Finland, Poland, Russia, Switzerland, Slovenia, the Czech Republic and Hungary.